Composite membranes with hydrophilic nanopores derived from the self-assembly of block copolymer supramolecular complexes. (January 2015) - Iannarelli, L.; Nisticò, R.; Avetta, P.; Lazzari, M.; Magnacca, G.; Calza, P.; Fabbri, D.; Scalarone, D.
Graphical abstract: Highlights: Nanoporous PS- b -PEO membranes were prepared on silicon patterned microsieves. A supramolecular strategy was followed to fabricate the nanoporous polymer layer. Normally oriented hydrophilic nanochannels span the entire membrane thickness. Membrane selectivity was proved by diffusion experiments. The composite membrane can be easily integrated in microfluidic devices. Abstract: Selective composite membranes with high and controlled porosity have been fabricated using patterned silicon microsieves as support and nanoporous polystyrene- block -poly(ethylene oxide) (PS- b -PEO) membranes as selective layer. The desired morphology of the block copolymer layer is obtained by a supramolecular approach based on the hydrogen bonding of the PEO block with resorcinol. The formation of PS- b -PEO/resorcinol complexes allows to easily control the self-assembly of the block copolymer and to obtain normally oriented PEO/resorcinol nanocylinders by spin coating PS- b -PEO/resorcinol solutions. In a further step resorcinol works as a porogen and by its selective dissolution densely packed, normally oriented nanochannels coated by PEO chains have been obtained. These hydrophilic nanochannels have a diameter of approximately 20 nm and cross the membranes from top to bottom. The nanoporous polymer layer is crack-free and well adheres to the support microsieve. The composite membrane is permeable to methylene blue while blocks larger molecules, such as bovine serum albumin.